Posterior microphthalmos and papillomacular fold-associated cystic changes misdiagnosed as cystoid macular edema following cataract extraction - Albar, Ahmad A (Clin Ophthalmol, 2015)
PURPOSE: Novel spectral-domain optical coherence tomography (SD-OCT) findings in posterior microphthalmos (PM) include cystoid changes in the papillomacular fold (PMF). These changes may be misdiagnosed as cystoid macular edema (CME) and may trigger unnecessary treatment including intravitreal injections. We report a case that underscores this scenario aiming to increase awareness of this entity among ophthalmologists. METHOD: A case report. RESULTS: A 25-year-old male presented with a history of clear lens extraction in both eyes as a refractive procedure. Postoperatively, he was diagnosed with CME and received five intravitreal bevacizumab injections in each eye as well as oral diamox for persistent cystic spaces noted on OCT. He was referred to our institution with the diagnosis of non-responding CME. A complete ophthalmic evaluation, including ultrasonography and SD-OCT, confirmed the diagnosis of PM and PMF with cystic cavities in the PMF. A fluorescein angiogram disclosed absence of macular leakage or optic nerve head staining indicating that the cystic cavities seen on SD-OCT are not due to postoperative CME but are rather the intrinsic cystic changes commonly seen in eyes with PM and a PMF. These cystic cavities were incorrectly thought to represent postoperative CME, which triggered the unnecessary treatment and lack of response. CONCLUSION: Cystic-like cavities are a component of the PMF in PM eyes and may be misdiagnosed as CME, especially in a postoperative setting. This case underscores the importance of understanding the intrinsic features of the PMF in eyes with PM and may help increase awareness among ophthalmologists of such a potentially confusing scenario.